Effectiveness of Soursop Leaf Extract in Reducing Glucose Levels in Diabetes Mellitus Patients: Literature Study - Elisa Issusilaningtyas; Nikmah Nuur Rochmah (Journal of Pharmacopoeia, 2024)
Alternative treatment for lowering sugar levels can be done through the use of herbal plants such as soursop leaves. This study aims to evaluate the effectiveness of soursop leaf extract (Annona muricata L.) in reducing blood glucose levels in Diabetes Mellitus (DM) patients. This research uses a literature study method, with data taken from scientific articles or journals within the last five years. Data was collected using the Google Scholar search engine with the keywords "diabetes mellitus," "soursop leaf extract," and "reducing sugar levels". Research shows that soursop leaf extract (Annona muricata L.) contains flavonoids, tannins, alkaloids, and saponins which are effective in lowering blood glucose levels through various mechanisms, including inhibiting sugar absorption, increasing glucose tolerance, stimulating insulin release, and regulating carbohydrate metabolism enzymes. The results of clinical and in silico trials support the effectiveness of this extract, making it a potential herbal treatment alternative amidst the current high costs of diabetes care. This research encourages the use of soursop leaves as a promising therapy and recommends further research to optimize its benefits.